1968
DOI: 10.1083/jcb.38.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Respiration and Mitochondrial Content in Single Neurons of the Supraoptic Nucleus

Abstract: The study was undertaken to investigate the possible correlation of total volume of mitochondria per cell with the rate of succinate oxidation in isolated nerve cell bodies, after various functional stresses in the experimental animals. Significant cytological effects were found in the nerve cells of the supraoptic nucleus in rats which had been thirsting for 4-12 days or had been given 2% sodium chloride solution as a substitute for drinking water for a few weeks. Quantitation of mitochondria was done from el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…For example, we found that in adult animals the mean percentage of perikaryal volume occupied by mitochondria was very similar in large light and in small dark neurons, as also found by Gabella et al (1988) in the sheep superior cervical ganglion. We also found that the mitochondria occupied 8.70% of the perikaryal volume, similar to percentages reported for other regions of the nervous system in adult animals (rabbit hypoglossal nucleus: Hudson et al, 1961; rat supraoptic nucleus: Eneström and Hamberger, 1968; rat olfactory bulb: Hinds and McNelly, 1979; sheep superior cervical ganglion: Gabella et al, 1988). However, larger percentages have been reported for other sites (rat auditory cortex: Peters and Vaughan, 1981;rat spinal Fig.…”
Section: Discussionsupporting
confidence: 89%
“…For example, we found that in adult animals the mean percentage of perikaryal volume occupied by mitochondria was very similar in large light and in small dark neurons, as also found by Gabella et al (1988) in the sheep superior cervical ganglion. We also found that the mitochondria occupied 8.70% of the perikaryal volume, similar to percentages reported for other regions of the nervous system in adult animals (rabbit hypoglossal nucleus: Hudson et al, 1961; rat supraoptic nucleus: Eneström and Hamberger, 1968; rat olfactory bulb: Hinds and McNelly, 1979; sheep superior cervical ganglion: Gabella et al, 1988). However, larger percentages have been reported for other sites (rat auditory cortex: Peters and Vaughan, 1981;rat spinal Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In the spinal ganglion neurons of young adult rabbits the mitochondria occupied 10.6% of the perikaryal volume. This percentage is similar to those reported for other regions of the nervous system: hypoglossal nucleus of the rabbit [8], supraoptic nucleus of the rat [3], olfactory bulb of the rat [7] and superior cervical ganglion of the sheep [4]. By contrast, distinctly larger values (about 14% and 21%, respectively) have been reported in pyramidal cells of the rat auditory cortex [17] and in ventral horn neurons of the rat spinal cord [9].…”
Section: Percentage Volume Of Mitochondria In Young Adult Rabbitssupporting
confidence: 88%
“…The appearance of this shorter T 2 peak has also been noted by others (4–6, 20), and it is possible that this component represents a distinct microanatomical reservoir. Multilammelar mitchondria for instance, which occupy more than 10% of the cytoplasmic volume in a nerve cell (28), offer a potential compartment that would likely have short relaxation times arising from elevated manganese content in mitochondrial fractions (29). This shortest T 2 has also been previously assigned to spurious nonaqueous signal (4, 6), and to an artifact arising from fitting to a distribution of myelin water T 2 times (5).…”
Section: Discussionmentioning
confidence: 99%